Outcome of trauma-related emergency laparotomies, in an era of far-reaching specialization - Hietbrink, Falco (World J Emerg Surg, 2019)
BACKGROUND: Far reaching sub-specialization tends to become obligatory for surgeons in most Western countries. It is suggested that exposure of surgeons to emergency laparotomy after trauma is ever declining. Therefore, it can be questioned whether a generalist (i.e., general surgery) with additional differentiation such as the trauma surgeon, will still be needed and can remain sufficiently qualified. This study aimed to evaluate volume trends and outcomes of emergency laparotomies in trauma. METHODS: A retrospective cohort study was performed in the University Medical Center Utrecht between January 2008 and January 2018, in which all patients who underwent an emergency laparotomy for trauma were included. Collected data were demographics, trauma-related characteristics, and number of (planned and unplanned) laparotomies with their indications. Primary outcome was in-hospital mortality; secondary outcomes were complications, length of ICU, and overall hospital stay. RESULTS: A total of 268 index emergency laparotomies were evaluated. Total number of patients who presented with an abdominal AIS > 2 remained constant over the past 10 years, as did the percentage of patients that required an emergency laparotomy. Most were polytrauma patients with a mean ISS = 27.5 (SD ± 14.9). The most frequent indication for laparotomy was hemodynamic instability or ongoing blood loss (44%).Unplanned relaparotomies occurred in 21% of the patients, mostly due to relapse of bleeding. Other complications were anastomotic leakage (8.6%), intestinal leakage after bowel contusion (4%). In addition, an incisional hernia was found in 6.3%. Mortality rate was 16.7%, mostly due to neurologic origin (42%). Average length of stay was 16 days with an ICU stay of 5 days. CONCLUSION: This study shows a persistent number of patients requiring emergency laparotomy after (blunt) abdominal trauma over 10 years in a European trauma center. When performed by a dedicated trauma team, this results in acceptable mortality and complication rates in this severely injured population.